Measurement of the Bs0 lifetime and production rate with Ds- ℓ+ combinations in Z decays - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1995)
A precise determination of the effective Bs0→K+K− lifetime can be used to constrain contributions from physics beyond the Standard Model in the Bs0 meson system. Conventional approaches select B meson decay products that are significantly displaced from the B meson production vertex. As a consequence, B mesons with low decay times are suppressed, introducing a bias to the decay time spectrum which must be corrected. This analysis uses a technique that explicitly avoids a lifetime bias by using a neural network based trigger and event selection. Using 1.0fb−1 of data recorded by the LHCb experiment, the effective Bs0→K+K− lifetime is measured as 1.455±0.046(stat.)±0.006(syst.)ps.